Pengaruh Penggunaan Asap Cair Grade 2 dari Kayu Kusambi dan Lama Simpan terhadap Kualitas Organoleptik dan Mikrobiologi Daging Se’i Sapi - Sarifudin, Kasimir (Universitas Nusa Cendana, 2023)
This study aims to determine the effect of using grade 2 liquid smoke from kusambi wood (Schleichera oleosa Merr) on the organoleptic and microbiological quality of se'i beef. The first factor studied was the concentration of grade 2 liquid smoke from kusambi wood; A0 = without liquid smoke (control), A1 = 0.5%; A2 = 2.5%; and A3 = 7.5%, while the second factor is storage time: S0 = 0 days, S5 = 5 days, and S10 = 10 days. The parameters measured were the organoleptic and microbiological quality of se'i beef. Application of liquid smoke on se'i beef with different concentrations at the specified storage time produces se'i beef products with different average colors, aromas, tastes, tenderness scores, and inhibition zone. The concentration of grade 2 liquid smoke from kusambi wood and the length of stored time affected the organoleptic quality and inhibition of the growth of Salmonella bacteria colonies. The higher the concentration of liquid smoke, the number of bacterial colonies decreases and the larger the diameter of the inhibition zone. The longer the meat is stored, the more colonies will grow. There was no significant difference in zone diameter on the concentration range tested.